Futuros Matemáticos e suas concepções sobre o conhecimento matemático e seu ensino - Meneghetti, Renata Cristina Geromel [UNESP]; Trevisani, Fernando de Mello [UNESP] (My University, 2013)
Taking referential theoretical conceptions of mathematical knowledge present in some of the main mathematics philosophical currents and considering that the teacher´s practice is influenced by his conception of mathematical knowledge, this research aims to understand the conceptions of mathematical knowledge and its teaching and learning teaching of future mathematicians. It follows a qualitative approach (case study) in which the data were collected by semi-structured interviews and document analysis. This investigation has pointed out that Mathematics together with Mathematics Teaching (or part of this: on the didactic and pedagogical knowledge of how to teach) could be important to formation of the future mathematician, who will probably teach in a college or university.

Neste trabalho busca-se compreender as concepções de conhecimento, ensino e aprendizagem de matemática de futuros matemáticos. Para tal, apresentamos concepções de conhecimento matemático vigentes em algumas das principais correntes filosóficas da matemática, uma vez que se considera que a prática do professor de matemática sofre influência da forma esse concebe o saber matemática. A pesquisa seguiu uma abordagem qualitativa, estudo de caso, e foi efetuada por meio de entrevistas semiestruturadas e análise documental. Através desta pesquisa, indica-se que o Bacharelado agregado à Licenciatura (ou à parte desta: referente aos conhecimentos didático-pedagógicos de como ensinar) poderia favorecer uma formação mais adequada ao futuro matemático.
Future mathematicians and their conceptions of the mathematical knowledge and its teaching and learning
Keywords: Mathematics knowledge; Mathematics teaching and learning; Mathematics degree; Conhecimento matemático; Ensino eaprendizagem de matemática; Bacharelado em matemática